Ephemeroptera na Mata Atlântica: tendências altitudinais e congruência taxonômica entre ninfas e imagos - Dotto, Caio Fernando (Universidade Federal de São Carlos, 2025)
Freshwater ecosystems and their biodiversity have been profoundly affected by anthropogenic activities. In this context, biomonitoring programs aimed at mitigating these impacts and conserving these environments have gained increasing prominence. This dissertation examines the use of insects from the order Ephemeroptera as ecological indicators and is structured in two chapters. The first chapter presents a systematic review of the literature on the relationship between altitude and Ephemeroptera diversity. The results revealed significant methodological and regional variation among studies, as well as a general trend of decreasing taxonomic richness with increasing altitude. The analysis of 74 scientific articles showed a geographic concentration of research in the Palearctic and Neotropical regions, primarily at lower elevations and with limited spatial coverage. Additionally, there was a notable lack of studies focusing exclusively on Ephemeroptera, highlighting key gaps for future research. The second chapter assessed Ephemeroptera assemblages in first- to third-order streams within the Atlantic Forest, as well as the taxonomic congruence between the nymph and imago stages, to evaluate their suitability as surrogates in biomonitoring programs. A total of 40 streams were sampled, revealing higher richness and abundance in nymphs compared to imagos. The congruence between the two life stages was low and not statistically significant, as were their correlations with environmental variables, indicating that nymphs and imagos respond differently to ecological conditions. Conversely, within the same life stage, measures of abundance and incidence were found to be interchangeable. These results underscore the importance of integrated approaches that combine multiple metrics and life stages to enhance the accuracy and effectiveness of ecological and biomonitoring studies.
Ephemeroptera in the Atlantic Forest: altitudinal trends and taxonomic congruence between nymphs and adults
Ephemeroptera en la Mata Atlántica: tendencias altitudinales y congruencia taxonómica entre ninfas y adultos
Keywords: Insetos aquáticos; Ecossistemas de água doce; Gradiente altitudinal; Riqueza de espécies; Congruência taxonômica; Ephemeroptera; Aquatic insects; Freshwater ecosystems; Altitudinal gradient; Species richness; Taxonomic congruence; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; 14. Vida na Água; 15. Vida Terrestre